Design of a microcomputer-based x-ray diffractometer controller - Naval, Prospero C. (1988)
This work describes the design of an APPLE II-based x-ray diffractometer controller capable of acquiring and analyzing x-ray powder diffraction data. The controller's interrupt-driven hardware includes an on-board scaler for counting x-ray pulses, a closed-loop stepper motor driver for Philips PW1050 Vertical Goniometer, and circuits for preset count data collection and safety. ACQUIRE - a data acquisition program for the controller coordinates its various devices so that it can perform sample scanning in any of the following modes: continous, preset time or preset count scanning. Thsi program watches over the scanning process and will try to correct any error it detects. Any fault monitored is logged on disk. The collected diffraction data is stored on disk together with its data acquisition parameters and may be transported to another computer. Data analysis is done by ANALYZE, a program that operates on the output file generated by ACQUIRE. Its 15 single-keystroke commands permit panning and zooming of the sample's diffractogram, data smoothing, data peak search, peak report generation, and digital plotting. Data smoothing uses a 3rd-dgree Savitzky-Golay Convoluting Filter of user-defined width. For peak detection the peak search algorithm examines the diffractogram's 2nd derivative for any Gaussian resemblance and checks the peaks' area for statistical significance. The hard copy plot is available from any on-line digital plotter supporting EPSON's Mode 0 Plotter Commands.
Typescript.
Thesis (M.S.)--University of the Philippines, Diliman.
Keywords: X-ray diffractometer